Working Fluid Selection and Performance Evaluation of ORC - Thurairaja, K.; Wijewardanea, A.; Jayasekaraa, S.; Ranasinghe, C. (Elsevier, 2018)
Organic Rankine Cycle (ORC) is known as one of the best method amongst the other low-grade energy recovery methods. ORC can be applied for different applications such as geothermal, solar thermal and waste heat. However, the application of ORC in these applications requires the selection of suitable working fluid for better performance. So, this paper focuses on performance evaluation of ORCs for different working fluids. The modelling work was performed using MATLAB and, a thermo-physical database, REFPROP. The evaluation is performed based on the performance of the working fluid. The results reveal that MD2M & cyclopentane for temperature ranges 50 - 100 ⁰C, butane, neopentane & R245fa for 100 - 150 ⁰C, ethanol, methanol and propanone for 150-200 ⁰C and Water, m-Xylene and p-Xylene for 200 - 320 ⁰C are better working fluids for energy extraction.
Keywords: Working fluid selection; Organic Rankine cycle